Atmospheric CO2 emissions and ocean acidification from bottom-trawling - Atwood, Trisha B.; Romanou, Anastasia; DeVries, Tim; Lerner, Paul E.; Mayorga, Juan S.; Bradley, Darcy; Cabral, Reniel B.; Schmidt, Gavin A.; Sala, Enric (Frontiers in Marine Science, 2024)
Trawling the seafloor can disturb carbon that took millennia to accumulate, but the fate of that carbon and its impact on climate and ecosystems remains unknown. Using satellite-inferred fishing events and carbon cycle models, we find that 55-60% of trawling-induced aqueous CO2 is released to the atmosphere over 7-9 years. Using recent estimates of bottom trawling's impact on sedimentary carbon, we found that between 1996-2020 trawling could have released, at the global scale, up to 0.34-0.37 Pg CO2 yr -1 to the atmosphere, and locally altered water pH in some semi-enclosed and heavy trawled seas. Our results suggest that the management of bottom-trawling efforts could be an important climate solution.